HUBUNGAN SELF ESTEEM DENGAN SIKAP SOSIAL REMAJA SERTA IMPLIKASINYA DALAM LAYANAN BIMBINGAN DAN KONSELING DI SMA DABIAH PADANG - Nidia Suryani (Universitas Muhammadiyah Tapanuli Selatan, 2017)
This research was initiated by the fact that was no self esteem in students based on their environmental condition.there were several factors influencing this condition;they were peer, past experience, mindset, gender, social status. Achievement, value, belief, and parenting. The objectives of this research were describing self esteem, describing social attitude, understanding the correlation betwewn self esteem and social attitude, and understanding its implication on guidance and counseling services. This research used quantitave method with correlational descriptive type.population of this research was 248 students of SMA Adabiah II Padang. Its samples were 186 students who were chosen with random sampling technique. The result revealed that generally students self esteem was in low category, students social attitude was in medium category, meanwhile, the correlation between self esteem and social attitude was negative in which r count ≤ r table, so Ho was accepted or independent variable had no significant correlation with dependent variable. Concering its implication, guidance and counseling services could be carried out in the form of information services, content mastery, and students group guidance services conducted for each class. It was expected that this implication can be used as an input for guidance and counseling teachers in order to improve the students self esteem and their social attitude.